Description and analysis of an interdisciplinary project on Covid-19: a scientific dissemination proposal from the 3MT genre - Abreu-Tardelli, Lilia Santos [UNESP] (2024)
The aim of this article is to describe a project for the scientific dissemination of videos about Covid-19 focusing on primary school students (6 to 11 years old) in a school in the northwest of S & atilde;o Paulo state. It also aims to present the results of the analysis of two of the scripts and videos, highlighting linguistic and multimodal aspects based on the theoretical -methodological framework of Sociodiscursive Interactionism (ISD) and the didactic genre model (3MT), in order to verify similarities and differences with the genre model of the 3MT proposed by Abreu-Tardelli (2020; 2021). The criteria for the videos' selection was the ones that had the highest number of views on YouTube. The analysis highlights the presence of explicative sequences, voices in direct speech to present the problematization and resolution phase, and the use of comparisons of the theme with familar locations and comparisons of scientific terms with everyday actions, showing a close approximation with the proposal of 3MT. It also contributes to health literacy, as they highlight the importance of considering language usage strategies to be understood by the target audience, as proposed by the 3MT.